2022
DOI: 10.3390/v14102091
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genomic Sequence Analysis of Domestic Cat Hepadnavirus in the United States

Abstract: Hepadnaviruses are partially double-stranded DNA viruses that infect a variety of species. The prototypical virus in this family is the human hepatitis B virus, which chronically infects approximately 400 million people worldwide and is a risk factor for progressive liver disease and liver cancer. The first hepadnavirus isolated from carnivores was a domestic cat hepadnavirus (DCH), initially identified in Australia and subsequently detected in cats in Europe and Asia. As with all characterized hepadnaviruses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…Furthermore, a link between DCH and liver injury could justify the development of novel antivirals and vaccines for cats. Similarities between HBV and DCH DR/epsilon regions identified in this study, and the predicted viral receptor [ 11 ], support similar approaches to target DCH therapeutically. Unfortunately, many nucleoside/nucleotide analogues—the mainstay of human HBV antiviral treatment—are unacceptably toxic to cats [ 30 ].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Furthermore, a link between DCH and liver injury could justify the development of novel antivirals and vaccines for cats. Similarities between HBV and DCH DR/epsilon regions identified in this study, and the predicted viral receptor [ 11 ], support similar approaches to target DCH therapeutically. Unfortunately, many nucleoside/nucleotide analogues—the mainstay of human HBV antiviral treatment—are unacceptably toxic to cats [ 30 ].…”
Section: Discussionsupporting
confidence: 70%
“…This study showed that DCH is circulating among cats in Hong Kong, with a molecular prevalence of 11.1%, as measured by DCH DNA detection in whole blood. The prevalence in other regions varies widely, with DCH-positive cats apparently uncommon in the USA (0.2%) [ 11 ], Japan (0.78%) [ 12 ], and UK (1.9%) [ 10 ]; whereas virus DNA has been readily detected in cats in Australia (6.5%) [ 6 ], Italy (10.8%; 4.2%) [ 7 , 26 ], Thailand (18.5%) [ 15 ], and Malaysia (12.3%) [ 9 ]. Despite study design differences, it is likely that there are genuine regional differences in DCH prevalence, potentially caused by various transmission dynamics, as with human HBV [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2018, an HBV-like virus, domestic cat hepadnavirus (DCH), was identified in domestic cats in Australia and was associated with feline chronic hepatitis (Aghazadeh et al, 2018), suggesting a similarity with HBV pathogenesis. Subsequently, DCH was identified in other countries, including Italy (Lanave et al, 2019), Thailand (Piewbang et al, 2020), Malaysia (Anpuanandam et al, 2021), United Kingdom (Jeanes et al, 2022), United States (Stone et al, 2022), Hong Kong (Capozza et al, 2023), and Japan (Takahashi et al, 2022). DCH has a partially double-stranded, circular DNA genome of ~3,200 bases in length (Aghazadeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%